MEASUREMENT UNITS - RONZELLI JÚNIOR, Pedro (Scientia Agraria, 2000)
The importance and necessity of the uniformed units use and presentation in papers were the reasons to this bibliography revision. The goal was to contribute to raise in quality the manuscripts and become cosmopolitan the acceptation of the publications. It was done an analysis about the rules of the International System of Units (SI) in Brazil, published by the Conselho Nacional de Metrologia, Normalização e Qualidade Industrial (CONMETRO), with comments about how to write correctly and also presented some tables with the base units, supplementary units, derived units, multiple and submultiples of these units, tolerated units out of the SI and some of the more utilized units in agrarian sciences.